Recent Trends in River Corridor Management Select Proceedings of RCRM 2021 - Chembolu, Vinay; Dutta, Subashisa; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents the select proceedings of the 1st International Conference on River Corridor Research and Management (RCRM 2021). It describes various topics on fluvio-hydro-ecological processes of river systems. The topics covered include river dynamics and morphological changes, river health and ecological aspects and satellite remote sensing for river corridor studies. The book also discusses the morphological behavior of gravel and sand-bed rivers, hydrological and hydraulics modeling and other important aspects of riverine ecology. The book will be a valuable reference for research scholars, academicians, river scientists and practitioners working in the areas of river science.
Geomorphic controls on sediment mobility and channel stability of a riffle-pool gravel bed channel -- Environmental planning of river corridors considering climate change: A brief perspective -- Assessment of fluvial controls and cross-sectional recovery indicators in a large regulated river -- Holistic Environmental Flow Assessment by Building Block Method in Inaccessible Himalayan River Basins -- Significance of Dam altered Vis-à-vis free flowing stretches of a Himalayan river, Teesta with special reference to Icthyofaunal Diversity: Importance towards riverine fisheries sustainability -- Impact of barricades on habitat and fish migration in river Cauvery, India -- Impacts on reproductive biology of Golden Mahseer caused by climate and land use change in western Himalaya -- Critical Mixing Depth models for Eutrophicated Inland Water Bodies to Prevent Harmful Cyano-Bacterial Blooms -- Significance of representing buildings in urban flood simulations -- Three-dimensional hydrodynamic modelling of permeable and impermeable river training works using CCHE 3D model and laboratory experiments -- Numerical and experimental investigation of effect of green river corridor on main channel hydraulics -- Flood Inundation Modelling Using Coupled 1D-2D HEC-RAS Model in Lower Kosi River Basin, India with Limited Data -- A study of the impact of some land use land cover changes on watershed hydrology -- Modelling of sediment yield of Tawi catchment to identify the critical sources area -- Use of Landsat and Sentinel-1 data for implementation of bank protection work in Brahmaputra river -- Potentially dangerous glacial lake risk mapping and assessment in Satluj river basin, Himachal Pradesh using remote sensing and GIS -- A Geospatial Approach for Mapping and Delineation of Palaeochannels of Ghaggar Basin, North-West India, for Groundwater Development to Meet Sustainable Development Goals.
Keywords: Environmental engineering; Civil engineering; Hydraulic engineering; Rock mechanics; Soil mechanics; Environmental Civil Engineering; Hydraulic Engineering; Soil and Rock Mechanics; Stream ecology -- Congresses; Rivers -- Congresses